Dampak Penggunaan Media Sosial pada Perilaku Sosial Media Generasi Milenial - Yunianto, Askar; Purwatiningtyas, P; Supriyanto, Aji; Listiyono, Hersatoto (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The millennial generation is a demographic group born between 1980 – 2000. As a generation that has grown up with rapid technological development, millennials have unique patterns of digital entertainment and development, millennials have unique patterns of digital entertainment and social media consumption. Understanding their preferences in these area is importantan for entertainment industry in developing effective content and platform strategies. This Study aims to analyze the pattern of digital entertainment and social media consumption, as well as preference for interaktive content, trends, and potential involment in content creation among the millennial generation. This research used a quantitative approach by distributing online survey to 110 millennial respondens. The collected data includes the use of digital entertainment platforms, sosial media, preferences for interactive content and trends, as well as interst in content creation. This research result show that the most widely used digital entertainment platforms among millenials are YouTube, Netfix, and Instagram. Meanwhile the most popular social media platforms are instagram, TikTok, and twitter. Millennials also a high preference for interaktive content and following ternd. Futhermore, there is quite a large potential for millennials to be involved in entertainment conten creation, with a high interest in participating in relevant training. This study provides valuable insights into the patterns of digital entertainment and social media consumption, as well as the preference and potential for content creation among the millennial generatin. These findings can help the entertainment industry in designing content and platform strategies that are more tailored to the needs of the millennial audience.